Effects of Academic Quality and Service Quality on University Students’ Satisfaction/ Hanis Aqilah Rusnipa ... [et al.] - Hashim, Marshita; Sa'ad, Shukriah; Rusnipa, Hanis Aqilah (Universiti Teknologi MARA Cawangan Sarawak, 2021)
This study was conducted on the premise that Higher Education Institutions (HEIs) with strong reputation have superior market positions in the higher education sector. It empirically examined academic quality, service quality, and student's satisfaction in the context of HEIs. The investigation was conducted using quantitative research. Four hundred twenty-six questionnaires were collected from students in public and private HEIs in Klang Valley. Correlation analysis and multiple regression were used to analyze the influence of variables and hypotheses testing for the study. The findings showed a significant relationship between academic quality and service quality with students' satisfaction. The results show that HEIs should continue to reinvest in their resources and skills to ensure that their institutions are in a better position to meet the needs of their students and, at the same time, improve the branding and reputation of their institutions. Future studies should include other factors that may influence HEIs’ reputations (both positively and negatively). The findings may provide valuable guidelines to Malaysian HEIs in improving specific areas of academics quality and service quality.